PHENOMENON OF THE QUALITY OF EDUCATION: THE BAROQUE EPOCH - Anton Kolomiiets (Borys Grinchenko Kyiv Metropolitan University, 2019)
The paper reviews recent approaches to the evaluation of education quality. The critical view of education quality in Ukraine today and its phenomenal success in the age of baroque is represented. Considerations for characteristic features of the education philosophy are founded on the analysis of Ukrainian and foreign authors' works. The conclusions concerning the reasons of the complications with the correct approach to evaluation of education quality on one hand and disadvantages of highly specialized education and its consequences on the other, outline the main issues of the article. The phenomenon of education quality of baroque age was reviewed from the position of the European educative system of Septem Artes Liberales. The Kyiv Mohyla Academy in XVII-XVII centuries was chosen as the most specifically Ukrainian historical example. The article indicated the importance of the formation of kinship of ideological foundations in the environment of educated aristocracy and the problems of both assessment of education quality and the degree of conformity of education to different social requirements. The comparison of cooperation of nowadays and baroque epoch erectors (as the architect and the customer) confirms big gap in their worldviews. Baroque's education, its phenomenon, or rather the phenomenon of its quality, and calling things in terms of the industrial age - efficiency and effectiveness, is the topic with enormous practical potential in terms not only and perhaps not so much of the historical point of view, when the purpose of the researcher is to study the past in search of «white spots», but also in terms of searching for the ways of preparing the successful «golden age» educators. The model suggested is suitable for realisation in modern Ukrainian education process